Medical Species Used in Russia for the Management of Diabetes and Related Disorders - Shikov, Alexander N.; Narkevich, Igor A.; Akamova, Alexandra V.; Nemyatykh, Oksana D.; Flisyuk, Elena V.; Luzhanin, Vladimir G.; Povydysh, Mariia N.; Mikhailova, Iuliia V.; Pozharitskaya, Olga N. (Frontiers in Pharmacology, 2021)
Background: Polyherbal mixtures called "medical species" are part of traditional and officinal medicine in Russia. This review aimed to analyze medical species used in Russia for the treatment of diabetes and related disorders. The information relevant to medical species, diabetes, and obesity was collected from local libraries, the online service E-library.ru, and Google Scholar. The prediction of the antidiabetic activity for the principal compounds identified in plants was performed using the free web resource PASS Online. Results: We collected and analyzed information about the compositions, specificities of use, and posology of 227 medical species. The medical species represent mixtures of 2-15 plants, while the most frequently mentioned in the literature are species comprising 3-6 plants. The top 10 plants among the 158 mentioned in the literature include Vaccinium myrtillus L., Phaseolus vulgaris L., Taraxacum campylodes G.E. Haglund., Urtica dioica L., Rosa spp., Hypericum spp., Galega officinalis L., Mentha × piperita L., Arctium spp, and Fragaria vesca L. The leading binary combination found in medical species comprises the leaves of V. myrtillus and pericarp of P. vulgaris; leaves of V. myrtillus and leaves of U. dioica; and leaves of V. myrtillus and aerial parts of G. officinalis. In triple combinations, in addition to the above-mentioned components, the roots of T. campylodes are often used. These combinations can be regarded as basic mixtures. Other plants are added to improve the efficacy, treat associated disorders, improve gastrointestinal function, prevent allergic reactions, etc. Meanwhile, an increase in plants in the mixture necessitates advanced techniques for quality control. A feature of medical species in Russia is the addition of fresh juices, birch sap, seaweeds, and adaptogenic plants. Modern studies of the mechanisms of action and predicted activities of the principal compounds from medicinal plants support the rationality of polyherbal mixtures. Nevertheless, the mechanisms are not well studied and reported due to the limited number of compounds. Further investigations with calculations of synergistic or additive indices are important for strengthening the scientific fundamentals for the wider use of medical species in the therapy of diabetes.